Three‐State Thermochromic Smart Window for Building Energy‐Saving - Meiling Liu; Xiansheng Li; Wenshuo Zhang; Lanxin Li; Liang Li; Chengming Wang; Gang Pei; Bin Zhao; Chongwen Zou (Advanced Science)
Abstract Smart windows that dynamically regulate solar spectrum transmission to reduce energy consumption in heating, ventilation, and air conditioning systems are highly desirable. However, the limited amplitude of the regulation and narrow wavelength control often degrade the modulation performance of existing smart windows. To improve solar modulation and thermal management, here we propose a three‐state thermochromic smart window (TSSW) capable of modulation across the entire solar spectrum. The TSSW is mainly based on the unique phase transition properties of tungsten‐doped vanadium dioxide (W‐VO₂) and perovskite films, which can stepwise control the visible light and near‐infrared (NIR) transmittance separately, leading to the adaptive transitions between cold, warm, and hot states. Results indicate that the TSSW achieves a solar modulation rate of 23.5%, with indoor solar irradiance decreasing from 413.6 W/m2 in the cold state to 374.5 W/m2 in the warm state, and down to 189.1 W/m2 in the hot state. The simulation results show that the annual total energy demand can be reduced by up to 102.09 WJ/m2 in some typical regions. Compared to Low‐E glass and ordinary glass, this TSSW offers superior energy‐saving potential, making it an ideal solution for reducing building energy consumption.